Prevalence of motoric cognitive risk syndrome among older adults in Brazil and evaluation of effect modification by race - Martins, João Paulo [UNESP]; Fukushima, Fernanda Bono [UNESP]; Benatti, Leandra Navarro [UNESP]; Bazan, Rodrigo [UNESP]; Silva, Katherine Di Santi Correa da [UNESP]; Vidal, Edison Iglesias de Oliveira [UNESP] (SAGE Publications, 2025)
BACKGROUND: Motoric cognitive risk syndrome (MCRS) is a pre-dementia syndrome of growing interest, yet it remains understudied in Latin America with a significant lack of information on the interaction between its risk factors and race. OBJECTIVE: To estimate the prevalence of MCRS among older adults in Brazil, investigate its association with various clinical and sociodemographic variables, and explore the potential of effect modification by race. METHODS: This cross-sectional, population-based study was conducted among community-dwelling older adults in Brazil, with data collected between 2015 and 2016. The diagnosis of MCRS was established following the standard recommended by the original study that first described it. We used Poisson regression models to analyze the association between MCRS and a list of 21 variables identified from a systematic review. RESULTS: A total of 4677 participants aged 60 years and older were included. The prevalence of MCRS in the Brazilian population of older adults was 4.34% (95% CI: 3.20%-5.48%). Higher levels of education and physical activity showed protective associations with MCRS, while depression and stroke demonstrated risk associations. A significant cross-over interaction between race and depression regarding MCRS was observed, such that the association of depression with MCRS was approximately three times higher among White individuals than Black individuals. CONCLUSIONS: Our results challenge previous estimates that Latin America is the region with the highest prevalence of MCRS among older adults and signal the need for further studies to better investigate the modification of effect of the association between depression and MCRS by race.
Keywords: Alzheimer's disease; Brazil; dementia; depression; interaction; motoric cognitive risk syndrome; prevalence; race; risk factors